PENINGKATAN KONSENTRASI SITRAL MINYAK SEREH DAPUR (Cymbopogon citratus) MENGGUNAKAN DISTILASI VAKUM (Improvement of Citral Concentration of Lemongrass Oil (Cymbopogon Citratus) Using Vacuum Distillation) - Ermaya, Dewi; Meilina, Hesti; Sulaiman, Ismail; Safriani, Novi; Supardan, M Dani (Baristand Industri Banda Aceh, 2013)
Lemongrass oil is the one type of essential oil that has high economic value.This research purpose to learn the process continued to increase the levels of citral inlemongrass oil using vacuum distillation method. Vacuum distillation process oflemongrass oil was carried out at operating condition: temperature of 100 to 140 oC,pressures of 50 to 90 mbar and pH of 3 to 7. Gas chromatography-mass spectroscopy(GCMS) results show that vacuum distillation process increased the concentration of citralof lemongrass oil. The experimental results show that variations of temperature, pressureand pH influence on concentration of citral. The highest citral of 84.7% obtained atexperimental condition of temperature of 140 oC, pressure of 70 mbar and pH of 5.